Improving Business Performance and Sustainability of SMEs Through Moderating Role of Local Culture - Sugianingrat, Ida Ayu Putu Widani; Astrama, I Made; Wati, Ni Wayan Alit Erlina; Hartati, Putu Sri; Putra, Ida Bagus Nyoman Bala (Universitas Warmadewa, 2024)
One of the determining factors for the success rate of a business is the motivation of the owner, in this case, micro, small and medium enterprises. This research is to determine the effect of business motivation on MSME performance and the moderating role of the Tri Hita Karana dimension in improving business performance so as to have an impact on business sustainability. The population used in this study were 32,226 units of MSMEs in Denpasar City. To obtain the sample, the slovin formula was used with a precision of 10%. Based on the calculation results of the Slovin formula, a sample of 99.69 is obtained (rounded upBecomes100) respondents. The determination of the research sample was carried out in a simple random based on clusters. Data collection was carried out by distributing questionnaires to MSME owners in the city of Denpasar who were the research samples directly or through google forms. The research results obtained motivation has a significant positive effect on business performance, business performance has a significant positive effect on business continuity, and the Tri Hita Karana dimension which consists of Parahyangan, Pawongan, and Palemahan is unable to play a moderating role in the effect of business motivation on MSME business performance in Denpasar Bali.